5(3x-9)-6=5(x-3)+24

Simple and best practice solution for 5(3x-9)-6=5(x-3)+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-9)-6=5(x-3)+24 equation:


Simplifying
5(3x + -9) + -6 = 5(x + -3) + 24

Reorder the terms:
5(-9 + 3x) + -6 = 5(x + -3) + 24
(-9 * 5 + 3x * 5) + -6 = 5(x + -3) + 24
(-45 + 15x) + -6 = 5(x + -3) + 24

Reorder the terms:
-45 + -6 + 15x = 5(x + -3) + 24

Combine like terms: -45 + -6 = -51
-51 + 15x = 5(x + -3) + 24

Reorder the terms:
-51 + 15x = 5(-3 + x) + 24
-51 + 15x = (-3 * 5 + x * 5) + 24
-51 + 15x = (-15 + 5x) + 24

Reorder the terms:
-51 + 15x = -15 + 24 + 5x

Combine like terms: -15 + 24 = 9
-51 + 15x = 9 + 5x

Solving
-51 + 15x = 9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-51 + 15x + -5x = 9 + 5x + -5x

Combine like terms: 15x + -5x = 10x
-51 + 10x = 9 + 5x + -5x

Combine like terms: 5x + -5x = 0
-51 + 10x = 9 + 0
-51 + 10x = 9

Add '51' to each side of the equation.
-51 + 51 + 10x = 9 + 51

Combine like terms: -51 + 51 = 0
0 + 10x = 9 + 51
10x = 9 + 51

Combine like terms: 9 + 51 = 60
10x = 60

Divide each side by '10'.
x = 6

Simplifying
x = 6

See similar equations:

| 2x^2+2x=264 | | -1-2w=-4 | | -3-(-5-2n)-6(1-5n)=9 | | 9+8m=6m-3 | | 2x-9+6x=-3(3+5x) | | [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 |

Equations solver categories